Malaysian telecommunication customer voice retaliation from dissatisfied service experience: The mediating effect of negative emotion / Nor Irvoni Mohd Ishar - Mohd Ishar, Nor Irvoni (Institute of Graduate Studies, UiTM, 2018)
Understanding customer complaining behaviour is imperative in the current economic condition as it could serve as a signal to the deteriorating performance of any organisation. It is much more crucial for service organisation because customers tend to move from one organisation to another when dissatisfaction persists. What may worsen the situation is that customers do not only just complain, but they retaliate. For retaliation to surface, it requires a specific trigger, the emotion. Therefore, the aim of this study is to investigate the concept of customer retaliation in relation to dissatisfying service experience with the interplay of emotion. The study investigates the relationship between the three variables, and the mediation effect of negative emotional experience on the relationship between dissatisfied service experience and subscribers voice retaliation behaviour. Despite extensive research conducted on the topic, understanding on its overall concept is still scarce, over simplified, and does not reflect the full spectrum of the subject. Many of the studies conducted have been focusing only on certain aspects of behavioural responses, i.e. switch and negative word-of-mouth, and overlooks other possible aggressive response such as retaliation. Important pertinent concepts such as emotions are ignored, thus creating a knowledge vacuum as it fails to highlight the severity of such behaviour. These voids leave researchers and practitioners, with limited information in understanding the full spectrum of complaining responses. Therefore, it is imperative that voice retaliation be further investigated. Such an understanding is likely to enhance the existing body of knowledge on how dissatisfaction can be dealt with effectively, and a model of coping with dissatisfaction and retaliation can be conceptualized and tested…